Knowledge, Beliefs About Cervical Cancer Among Women of Childbearing Age in Abia State - Okafor, Elizabeth Chibuzor; Samuel, Effiong Sunday (International Journal of Human Kinetics, Health and Education, 2023)
The purpose of the study was to determine the knowledge, beliefs about cervical cancer among women of childbearing age (WCA) in Abia State. The descriptive survey research design was used for the study. The population of the study comprised of 766,723 WCA in Abia State. The sample size for the study consisted of 630 respondents, selected using multistage sampling procedure. The instruments for data collection were the researcher’s structured questionnaire and focus group discussion guide which were validated by three research experts from Department of Human Kinetic and Health Education, University of Nigeria, Nsukka. The reliability of the instruments was also established and reliability co-efficient of .74 was obtained. Data collected were analysed using means, frequencies and percentages. The results of the findings showed that the level of knowledge of cervical cancer by WCA were low (39.18%). Majority (89.8%) of WCA did not believe that cervical cancer is for old women, is never curable, is caused by evil spirits, witchcrafts or enemies and that screening is for married women only. There was significant difference in the level of knowledge of cervical cancer by WCA based on age and level of education, (p<0.05). Based on the findings, conclusions were drawn and it was recommended that WCA should be educated on cervical cancer to create awareness using cervical cancer prevention programme (CCPP) developed by the author.